Growth rate of Pseudomonas fluorescens in liquid fertilizer from brown seaweed (Sargassum sp.) extracts. (November 2019) - Basmal, J; Aribowo, M E; Nurhayati,; Kusumawati, R
Abstract: The purpose of this study was to observe the growth rate of Pseudomonas fluorescens bacteria as biological agents to stimulate plant growth and inhibit the growth of pathogenic bacteria. The method used were aimed to extract the micro, macro and growth stimulating substances contained in the thallus of Sargassum seaweed which had been fermented for 5 days using 0.3% KOH solution and then heated at 70°C for 2 hours. The filtrate obtained was formulated by adding silage and molasses which were then sterilized at 121°C for 15 minutes. The P. fluorescence bacteria were inoculated into the formulation solution and observed for 20 days with a span of 5 days against pH values, thickness, total nitrogen, Corganic, electric conductivity (EC), total dissolved of solid (TDS) and growth rate of P. flourescens. The results showed that the pH value did not show significant differences but the viscosity value, total nitrogen, Corganic, EC, TDS, and TPC were significantly different. The best results were found on the 10 th day of inoculation of P. fluorescence in a non-sterile formulation solution with a pH value of 3.76, thickness of 2.95 cPs, total N-0.62%, Corganic 0.1%, EC 9, 814 μS / cm, TDS 4, 602 ppm and Total Plate Count of 10.6 log CFU/ml.